Development of the finishing and strengthening technological operations using SADT-technologies - Kusyi Yaroslav; Lychak Oleh; Topilnytskyy Volodymyr; Bošanský Miroslav (Lviv Politechnic Publishing House, 2019)
The rational design of technological processes of parts manufacturing in single and small-scale production is inefficient without wide introduction of modern tools of part manufactu ring automation with modern computer-based equipment and software. It is desirable to carry out of automated synthesis of single route technological processes with minimal influence of the operator on the technological environment. The technology of computer-aided design of technological processes is used to develop effective algorithms of functioning of adapted systems for control of technological processes and their mplementation when taking into account interrelations with the technological environment. Automated development of technological environments of a given level of design concerning a dedicated technical system is possible on the basis of their rational functional models, created by means of CALS-technologies. The rational use of the SADT methodology with application of the principle of decomposition and development of the SADT-diagrams allows to solve the given technical problems. Therefore, the purpose of this paper is to develop and study the vibrational centrifugal surface strengthening at the finishing and hardening technological operation to provide the required quality parameters and operational characteristics of the parts. The object of this research is a finishing and hardening technological operation. The subject of this research is method and parameters of vibrational-centrifugal surface strengthening to provide the required quality parameters and operational characteristics of the parts. The development of SADT diagrams allows to divide the technological process to technological operations, cutter–setting positions, technological steps, main machining steps etc. In this paper the principles of control of technological operation for vibration-centrifugal strengthening of surfaces of parts are suggested. The experimental device for machining of inner surfaces of parts is described. The initial and detailed model of the operation of the vibrational-centrifugal strengthening is offered. Statistical and structural analysis of technological process made it possible to establish the influence of the parameters of the vibrational-centrifugal strengthening on the geometric and physical mechanical parameters of the surface quality and associated operational characteristics. Further research in that field will be related on the development of practical recommendations for using of the vibrational centrifugal surface treatment for improving of the geometric and physical and mechanical parameters of parts surfaces.
Keywords: technology of computer-aided design of technological processes, life cycle of a part, SADT-technology, quality parameters, vibrational-centrifugal surface strengthening